2001
DOI: 10.1128/mcb.21.8.2767-2778.2001
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular and Intramolecular Interactions Regulate Catalytic Activity of Myotonic Dystrophy Kinase-Related Cdc42-Binding Kinase α

Abstract: Myotonic dystrophy kinase-related Cdc42-binding kinase (MRCK) is a Cdc42-binding serine/threonine kinase with multiple functional domains. We had previously shown MRCK␣ to be implicated in Cdc42-mediated peripheral actin formation and neurite outgrowth in HeLa and PC12 cells, respectively. Here we demonstrate that native MRCK exists in high-molecular-weight complexes. We further show that the three independent coiled-coil (CC) domains and the N-terminal region preceding the kinase domain are responsible for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 49 publications
(65 reference statements)
8
106
6
Order By: Relevance
“…4G; n18/22 indistinguishable from wild type). In vitro studies of mammalian CDC42BP demonstrate that this domain binds phorbol ester (Tan et al, 2001a). However, our data demonstrate that this interaction is not essential to Gek function.…”
Section: Research Articlecontrasting
confidence: 46%
See 1 more Smart Citation
“…4G; n18/22 indistinguishable from wild type). In vitro studies of mammalian CDC42BP demonstrate that this domain binds phorbol ester (Tan et al, 2001a). However, our data demonstrate that this interaction is not essential to Gek function.…”
Section: Research Articlecontrasting
confidence: 46%
“…Work in both contexts demonstrates that the kinase domain is the crucial effector of the protein, as deletion or inactivation of this domain removes all detectable activity both in vivo and in vitro (this work) (Luo et al, 1997;Leung et al, 1998). Previous studies of MRCK uncovered multiple negative regulatory mechanisms (Tan et al, 2001a;Tan et al, 2001b;Dong et al, 2002). In particular, the coiled-coil domain drives oligomerization and contains a kinase-inhibitory motif (KIM) that sequesters the kinase domain when the protein is inactive (Tan et al, 2001a;Dong et al, 2002;Garcia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be predicted that other kinases organized in a similar manner would also be subjected to activating mutations that affected Cterminal regulatory regions. Indeed, the Cdc42-regulated MRCKa (aka CDC42BPA), which has a similar role in actin cytoskeleton regulation as ROCK1 and ROCK2, has an example of a frameshift and termination at K697* in the HCC1395 breast ductal carcinoma cell line that removes autoinhibitory C1 and PH-like domains (Tan et al, 2001). Interestingly, four nonsynonymous mutations were identified for MRCKb (aka CDC42BPB), all of which occur C terminal to the kinase domain and therefore are potentially activating, with the mutation most likely to be activating consisting of a frameshift and termination at R1092* found in an intestinal adenocarcinoma tumor.…”
mentioning
confidence: 99%
“…DMPK is regulated by activation loop phosphorylation, dimerization and transautophosphorylation (Elkins et al, 2009). Although specific sites have not yet been identified, the residues Ser234, Thr240 and Thr403 conserved in DMPK and MRCKs, are probably implicated in DMPK activation (Tan et al, 2001;Wansink et al, 2003). In the following sections, the structural domains that comprise DMPK are described in detail.…”
Section: Structural Domains Of Dmpkmentioning
confidence: 99%
“…Both DMPK and ROCKs are able to form dimmers. Structural studies on DMPK, ROCKs, and MRCK have shown that dimerization depends on the regions N-and C-terminal immediately adjacent to the kinase domain (Doran et al, 2004;Garcia et al, 2006;Jacobs et al, 2006;Tan et al, 2001). DMPK is regulated by activation loop phosphorylation, dimerization and transautophosphorylation (Elkins et al, 2009).…”
Section: Structural Domains Of Dmpkmentioning
confidence: 99%